Pelatihan Perhitungan Pajak Penghasilan Pasal 21 Dengan Metode TER di SMK LP3 Istana Jakarta - Widyowati, Lestari Adhi; Ningsih, Sri Setia; Sihombing, Novfitri Landong Namora; Aam Aminah; Jalih, Jara Hardiyanti; Qadaar, Amiruddin (Jurnal Masyarakat Indonesia (Jumas), 2025)
The Law on Harmonization of Tax Regulations (UU HPP) mandates ongoing tax reform in the areas of organization, human resources, information and technology, databases, business processes and legal regulations. The government has issued a Government Regulation (PP) regarding Article 21 Income Tax (PPh), PP 58/2023, which is one of the tax reforms. Calculation of income tax article 21 is adjusted to PP no. 58 of 2023 and PMK no. 168 of 2023, is a change related to the latest tax regulations. The aim of the TER scheme is to help companies carry out calculations so that they can reduce the possibility of miscalculations when fulfilling their tax obligations. The aim of this community service activity is to overcome partners' problems, namely providing knowledge and training regarding income tax Article 21 and its calculations to teachers and vocational school students, especially accounting majors, so that they can equip students with knowledge of taxation with the latest regulations.